Between Sexism and Expressions of Resistance over the Body: A Study of Poster Texts in Demonstrations in 2022 - Setiyawan, Radius; Maulida, Maulida; Lestari, Sri (Journal of Urban Sociology, 2024)
In April and September 2022, students in various regions in Indonesia held demonstrations. These activities demanded and protested against the government's discourse on the policy of 3 presidential terms. Meanwhile, in September, there was an action against the increase in fuel prices. Like the previous demonstrations, the action used posters as a medium of public communication. What was interesting about the posters was the content of the demonstration. The content of the posters tended to be more related to the body and sexual matters. The content used more metaphors of everyday life related to sexual activity. This spread massively in many social media. Through Theo Van Leeuwen's critical discourse analysis method, this research discusses several sexist poster texts and analyzes the social context behind the phenomenon.  There are two assumptions that this paper tries to address. First, the poster content that appears is sexist content that demeans women. The second is that it is part of an expression of women's resistance to bodily restraint. Both arguments above will be reviewed in this paper. This research found that there was sexist content in posters that used direct or indirect expressions of sexism. The sexist expressions in the posters also show misogynistic practices because posters that denigrate women come from women. Findings also show that the sexist language used leads to pornography.Keywords: demonstration, poster, sexism, women, cda